EXTRAPONTINE MYELINOLYSIS WITH DAMAGE TO THE SUBCRORTIAL NUCLEARS OF THE BRAIN - Зуева, Светлана Алексеевна; Юрманова, Валентина Львовна; Портнов, Юрий Михайлович; Речкин, Виталий Николаевич; Семенов, Владимир Александрович; Елгина, Светлана Ивановна; Рудаева, Елена Владимировна; Мозес, Кира Борисовна (Medicine in Kuzbass, 2024)
Extrapontine myelinolysis (EPM) is a rare, severe and difficult to diagnose lesion of the central nervous system (CNS). Studies indicate that the prevalence of this disease ranges from 0.25 to 0.5 % in the general population and 2.5 % in intensive care units. We present a clinical case of EPM in a 63-year-old female patient due to dehydration with early manifestation of behavioral disorders and further development of the clinical picture of parkinsonism.